Integrating ethics, health policy and health systems in low and middle income countries : case studies from Malaysia and Pakistan. - Hyder, Adnan A; Meritt, Maria; Ali, Joseph; Tran, Nhan T; K.C Mani, Kulanthayan; Akhtar, Tasleem (World Health Organization, 2008)
Scientific progress is a significant basis for change in public-health policy and practice, but the field also invests in value-laden concepts and responds daily to sociopolitical, cultural and evaluative concerns. The concepts that drive much of public-health practice are shaped by the collective and individual mores that define social systems. This paper seeks to describe the ethics processes in play when public-health mechanisms are established in low- and middle-income countries, by focusing on two cases where ethics played a crucial role in producing positive institutional change in public-health policy. First, we introduce an overview of the relationship between ethics and public health; second, we provide a conceptual framework for the ethical analysis of health system events, noting how this approach might enhance the power of existing frameworks; and third, we demonstrate the interplay of these frameworks through the analysis of a programme to enhance road safety in Malaysia and an initiative to establish a national ethics committee in Pakistan. We conclude that, while ethics are gradually being integrated into public-health policy decisions in many developing health systems, ethical analysis is often implicit and undervalued. This paper highlights the need to analyse public-health decision-making from an ethical perspective.